Experimental thermal characterization of timber frame exterior wall using reed straws as heat insulation materials - Georgescu, Sergiu-Valeriu; Coşereanu, Camelia; Fotin, Adriana; Brenci, Luminiţa-Maria; Costiuc, Liviu (Springer Science and Business Media LLC, 2019)
The research presented in this paper proposes structures of timber frame exterior walls using reed straws as insulation materials. Having thicknesses of 175 mm and designed for exterior building walls, the proposed structures are composed of 12-mm-thick oriented strand board, 150-mm-thick insulation material with and without air layers, a vapour barrier foil and 12.5-mm-thick gypsum board for the interior face of the wall. The insulation materials used as reference for the proposed structures are polystyrene and rock wool. Reed straws used as insulation material for the tested wall structures formed insulation layers of 150 mm thickness in five configurations: 150-mm loose-fill reed straws without air layer and other four variants with loose-fill reed straws and 100-, 50-, 20- and 10-mm-thick air layers, respectively. The air layer was placed at the contact with gypsum board for all configurations. The reference structures (rock wool and polystyrene as insulation materials) followed three of the configurations set-up, namely 150-mm-thick insulation material (rock wool or polystyrene) only and insulation materials with air layers thicknesses of 100 and 50 mm, respectively. The eleven tested structures were subjected to thermal conductivity coefficient (lambda) measurements. The tests were performed on HFM436 Lambda equipment. The structures were tested for an entire cycle of temperatures varying between - 10 and 30 degrees C and thus simulating summer and winter climate conditions. The thermal conductivity coefficient of the exterior walls filled with loose reed straws as insulation material was recorded between mean values of 0.076 and 0.077 W m(-1) K-1, except the structure with an air layer of 100 mm, for which a value of 0.120 W m(-1) K-1 was registered.
Keywords: Wood frame; Wall structure; Thermal conductivity; Reed straws